Risk Management in UK Life Insurance Companies - Wirth, Pierre (2010)
Nowadays, efficient risk management is considered as a source of competitive advantage. By analysing annual reports and accounts of 12 UK Life insurers, this paper has for a goal to verify the existing findings of the literature and others surveys that have already analysed the risk management processes applied in this industry. Furthermore the other aims of this dissertation are to explore the evolution of the risk management practices from 2006 to 2008 considering EWRM, financial risk management, or the use of quantitative models. Then, the effect of the regulations on the risk management practices and finally verifying whether or not the size and type of company affects its risk management process will also be focused on. In order to achieve these objectives the method used is to qualitatively analyse reports and accounts and creating small individual case studies that will help to draw general conclusions thanks to adequate research questions. The main findings are that the risk management of UK life insurance companies is currently improving, that more and more insurers adopt an EWRM framework, that large insurers manage their risks better than small ones and that new regulations tend to improve the risk management and disclosure in general.